2008
DOI: 10.2139/ssrn.1105752
|View full text |Cite
|
Sign up to set email alerts
|

The Currency Equivalent Index and the Current Stock of Money

Abstract: The currency equivalent index provides an elegant method for measuring the stock of money, but it rests upon assumptions that do not match an important characteristic of the data. Thus, it is unclear what, if anything, the CE measures. This paper attempts to answer this question by deriving the current stock of money (CSM), which is dened to be the discounted present value of the monetary service ows provided by only the current portfolio of monetary assets, and then analyzing the assumptions under which the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…. N , Kelly (2008) showed that the current stock of money reduces to the currency equivalent index (Rotemberg et al, 1995). Thus under assumptions one through four, the current stock of money can be written as…”
Section: Measuring the Current Stock Of Moneymentioning
confidence: 99%
“…. N , Kelly (2008) showed that the current stock of money reduces to the currency equivalent index (Rotemberg et al, 1995). Thus under assumptions one through four, the current stock of money can be written as…”
Section: Measuring the Current Stock Of Moneymentioning
confidence: 99%